Analisis Semiotik dalam Memahami Bahasa Agama di Era Globalisasi - Eddy Setia; M Surip (Universitas Negeri Medan, 2019)
In linguistic studies, semiotics is perceived as a sign composed of two inseparable elements, namely signifiant and signifier. Signifiant is a linguistic material whereas signifier is a concept in mind. Language is metaphorical and, hence, the meaning it produces fluxes in accordance with its context. By such logic, if a religious language is a collection of texts (signs) then it does not contain an ultimate meaning. Therefore, under this context semiotics plays its significant role in which the religious texts bear new understandings to actualize the universal Islamic messages and bring the mission of mercy for the universe (rahmatan lil ‘alamin).